A long term restrained shrinkage study of concrete slabs on ground. (1st November 2015) - Shadravan, Shideh; Ramseyer, Chris; Kang, Thomas H.-K.
Highlights: Full-scale, real slabs-on-ground specimens were tested in a controlled environment. The temperature and humidity on the slab-on-ground were controlled, while it was exposed to the ground moisture on the bottom surface. A variety of data including joint movements, internal relative humidity and temperature over the slab depth were monitored. Typical shrinkage-reducing admixtures and calcium sulfoaluminate cements were experimentally evaluated. Abstract: This paper summarizes the results from an experimental study on the behavior of concrete slabs-on-ground in a controlled environment. The test program characterizes the dimensional properties of selected concrete materials, evaluating their performance as real slabs-on-ground in that they are exposed to the controlled environment on the top surface and to the ground moisture on the bottom surface. The concrete mix designs examined included normal-strength portland cement concrete ( PCC ), high-strength concrete ( HSC ), concrete using shrinkage reducing admixtures ( SRA ), and concrete using calcium sulfoaluminate cement ( CSA ). The data include standard concrete material characterization test results, joint movements, internal relative humidity and temperature over the slab depth. It was found that the concrete using CSA was very stable with no long term shrinkage, cracking or warping, while typical PCC and HSC continued to show crack growth at over 600 days of age. The concrete using SRA had a minor impact at early age and limited impact on long term sectional stability.